Pengaruh Integritas Aparatur Sipil Negara terhadap Kualitas Pelayanan di Dinas Perhubungan Kabupaten Agam - Mahdi, Tio Septia; Syamsir, Syamsir (Al-DYAS, 2024)
of service at the Agam Regency Transportation Office. This is indicated to be caused by integrity that is still not good. The purpose of this study was to obtain data and information on the influence of the influence of the integrity of the state civil apparatus on the quality of service in the Agam district transportation office. This type of research is quantitative research. The total population in this study was 60 employees. As for the number of samples, there are 60 employees. The research instrument used was a Likert Scale model questionnaire with four answer choices. Validity and reliability tests are carried out with the help of the SPSS program version 26. Then a simple regression analysis test was carried out between the two variables. The results showed that the integrity of the apparatus had a significant effect on the quality of service in the Agam Regency transportation office, which was 35.9% and the probability value (sig) was 0.000.